Young Africans' social representations of sexual abuse of power in their HIV-related creative narratives, 2005–2014: cultural scripts and applied possibilities. Issue 1 (2nd January 2019) - Singleton, Robyn; Winskell, Kate; McLeod, Haley; Gregg, Amy; Sabben, Gaëlle; Obong'o, Chris; Dia, Fatim
Abstract: The sexual abuse of power is a form of sexual coercion in which individuals – typically male – use their positions of authority to obtain sex. We analysed social representations of sexual abuse of power in a sample of 1, 446 narratives about HIV written by young Africans between 2005 and 2014. The narratives were prepared at five different points in time (2005, 2008, 2011, 2013 and 2014) by authors aged 10–24 in urban and rural areas of Swaziland, Kenya, South-East Nigeria, Burkina Faso and Senegal. We combined three analytical approaches: descriptive statistics of quantifiable characteristics of the narratives, thematic data analysis and a narrative-based approach. Analysis revealed two underlying cultural scripts describing the sexual abuse of power between (a) teachers and female students, and (b) male employers and domestic workers. Cross-national variation was evident in the emphasis authors placed on socio-contextual inequalities, particularly poverty, and on individual level blame. While a minority of Nigerian and Burkinabe authors depicted female characters creatively exercising agency and avoiding unwanted sex, overall there was little critique of underlying assumptions of male sexual entitlement and female responsibility for controlling male sexuality in the context of unequal control of resources. We outline recommendations for strategies to deconstruct these harmful scripts.